Chaperone-mediated autophagy protects against atherosclerosis. Issue 10 (3rd October 2022) - Madrigal-Matute, Julio; Cuervo, Ana Maria; Sluimer, Judith C.
ABSTRACT: Atherosclerosis, the leading cause of cardiovascular death, is driven by hyperlipidemia, inflammation and aggravated by aging. As chaperone-mediated autophagy (CMA), a selective type of lysosomal degradation for intracellular proteins, diminishes with age and is inhibited by lipid excess, we studied if the decline in CMA could contribute to atherosclerosis pathogenesis. We found that CMA declines in human and murine vasculature with disease progression. Inhibition and reactivation of CMA using transgenic mouse models establishes a protective effect of CMA against atherogenesis. CMA upregulation ameliorates both systemic metabolic parameters, and vascular cell function. Our work suggests CMA reactivation could be a viable therapeutic strategy to prevent and reduce cardiovascular disease.